Bisphenol AF and Bisphenol F Induce Similar Feminizing Effects in Chicken Embryo Testis as Bisphenol A. (3rd October 2020) - Mentor, Anna; Wänn, Mimmi; Brunström, Björn; Jönsson, Maria; Mattsson, Anna
Abstract: The plastic component bisphenol A (BPA) impairs reproductive organ development in various experimental animal species. In birds, effects are similar to those caused by other xenoestrogens. Because of its endocrine disrupting activity, BPA is being substituted with other bisphenols in many applications. Using the chicken embryo model, we explored whether the BPA alternatives bisphenol AF (BPAF), bisphenol F (BPF), and bisphenol S (BPS) can induce effects on reproductive organ development similar to those induced by BPA. Embryos were exposed in ovo from embryonic day 4 (E4) to vehicle, BPAF at 2.1, 21, 210, and 520 nmol/g egg, or to BPA, BPF, or BPS at 210 nmol/g egg and were dissected on embryonic day 19. Similar to BPA, BPAF and BPF induced testis feminization, manifested as eg testis-size asymmetry and ovarian-like cortex in the left testis. In the BPS-group, too few males were alive on day 19 to evaluate any effects on testis development. We found no effects by any treatment on ovaries or Müllerian ducts. BPAF and BPS increased the gallbladder-somatic index and BPAF, BPF and BPS caused increased embryo mortality. The overall lowest-observed-adverse-effect level for BPAF was 210 nmol/g egg based on increased mortality, increased gallbladder-somatic index, and various signs of testis feminization. This study demonstrates that the BPA replacements BPAF, BPF, and BPS are embryotoxic and suggests that BPAF is at least as potent as BPA in inducing estrogen-like effects in chicken embryos. Our results support the notion that these bisphenols are not safe alternatives to BPA.